Manifestations of the principle of functional equivalence and non-discrimination in the colombian legal system - Polanco López, Hugo Armando (2018)
On this article we analyze how the use of electronic communications has transformed the private contract law, with emphasis on the principle of functional equivalence and non-discrimination. Begins with the concept of e-commerce, classes of e-commerce, continues with the principles of the law of e-commerce, continues the uniform law of electronic commerce, and then study the main manifestations of the principle of functional equivalence and non-discrimination, such as: written document, original document, signed document, the admissibility of data messages as evidence and the use of electronic communications in the formation of contracts.